PP39 What is the risk of major trauma following a fall down stairs? – A systematic review. Issue 9 (19th August 2021) - Holt, Christopher; Keating, Samuel; Tonkins, Michael; Bradbury, Daniel; Fuller, Gordon
Abstract : Background: Specific mechanisms of injury are stated in pre-hospital triage tools to identify suspected cases of major trauma. Falls down stairs are common presentations in UK emergency departments, yet are frequently overlooked as a causative mechanism of major trauma. No prior systematic review has examined this association. Methods: Seven internationally recognised literature databases and seven grey literature databases were screened utilising a common search strategy from inception until 31 December 2019. Abstracts were screened for relevance by a single reviewer. Full texts were screened and subsequently extracted by 3 separate reviewers against strict inclusion/exclusion criteria. A risk of bias assessment based on GRADE recommendations was performed. In the absence of study heterogeneity, a narrative synthesis was planned. The reporting of this systematic review followed PRISMA 2009 statement guidelines. Results: 5240 articles were identified from database searching, 89 articles had their full texts assessed for eligibility and 6 articles were included for qualitative synthesis. All studies were retrospective in nature and originated from more economically developed countries. 7431 patients who fell down stairs were analysed, of which, 707 (9.5%) met major trauma definitions. Falls down stairs resulted in a significantly increased risk of serious injury compared to other fall mechanisms (OR: 1.621, 95% CI: 1.381 – 1.902, p<0.0005). Analysis of confounding factors demonstrated age (OR: 2.59, 95% CI: 1.57 – 4.28, p<0.001) and alcohol intoxication (OR: 2.6, 95% CI: 1.4 – 4.7, p=0.001) to be significantly associated with major trauma. Risk of bias was moderate to high across all 6 studies. Conclusion: This systematic review highlighted the paucity of literature surrounding the incidence of major trauma following falls down stairs. A retrospective cohort study is currently being undertaken to analyse the risk of major trauma following falls down stairs. On completion, the results will be incorporated with the results of this systematic review.